Extended DNA threading through a dual-engine motor module of the activating signal co-integrator 1 complex - Junqiao Jia; Tarek Hilal; Katherine E. Bohnsack; Aleksandar Chernev; Ning Tsao; Juliane Bethmann; Aruna Arumugam; Lane Parmely; Nicole Holton; Bernhard Loll; Nima Mosammaparast; Markus T. Bohnsack; et al. (Nature Communications, 2023)
ASCC3 is a multi-functional helicase that contains two consecutive Ski2-like helicase units. Here, the authors show that ASCC3 can unwind DNA by threading one strand of a substrate duplex through both helicase units, supported by the TRIP4 protein.